Climate change and water resources: An international perspective - Marianne Keudel (Universität zu Köln, Institut für Wirtschaftspolitik (iwp), 2007)
Climate change and its consequences are the focus of many environmental policies in the European Union but also in other countries. Whereas in the US marketable instruments like permit trading have already been implemented since the 1980s, the EU first implemented permit trading for CO2 emissions in 2005. Climate change also influences the availability of water resources; water levels of rivers in the EU are assumed to decrease in the next decades. Decreasing water levels, in turn, heavily influence the quality of these water resources. In some countries the instrument of permit trading is also applied to the regulation of water resources (quantity and quality). This paper gives an overview of existing systems in order to show how such trading systems can create incentives for the efficient use of resources by means of pricing.
Keywords: Q25; Q53; 330; river basin management; water trading; water quality trading; Wasserpolitik; Gewässerschutz; Emissionshandel; Australien; USA; EU-Staaten